FUNGSI PEMERINTAH DESA DALAM PEMBANGUNAN DI SEKTOR PERTANIAN: STUDI KASUS PADA DESA TALONTAM KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Gustiani, Lilis; Rafi, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research is based on problems related to the function of the village government in development in the agricultural sector, which includes irrigation which still does not irrigate all rice fields, the minimal APBDes budget in the agricultural sector and limited road access to rice fields in Talontam Village. Therefore, the aim of this research is to determine the function of the village government in development in the agricultural sector and the obstacles faced by the village government in development in the agricultural sector in Talontam Village, Benai District, Kuantan Singingi Regency. The research method used in this research is descriptive qualitative, where the location of this research is in Talontam Village, Benai District, Kuantan Singingi Regency. Then, the data collection techniques used were interviews and documentation. Meanwhile, data analysis was carried out using qualitative descriptive analysis techniques which describe data and information based on existing facts and then analyzed systematically. The results of this research show that the government's function in development in the agricultural sector in Talontam Village, Benai District, Kuantan Singingi Regency can be seen in several functions, namely; First, the development function is related to the creation of water channel irrigation, procurement of superior varieties of seeds and agricultural technology. Second, the service function is related to the distribution of fertilizer, seeds and control of pests and diseases. Third, the empowerment function in development in the agricultural sector is related to the existence of a guidance program for local farmers. Furthermore, there are several obstacles faced by the Talontam Village Government in development in the agricultural sector, namely the lack of APBDes in the agricultural sector, problems related to land area, problems in food productivity, climate change and a lack of agricultural infrastructure which causes the function of the village government in development in the agricultural sector is not yet optimal. Keywords: Government Functions, Village Government, Development, Agriculture.